Conceptual Model for e-Lesson Plan Management System - Zamzuri, Yahya (2010)
Networks communication is one of the technology widely use today, with networks communication it can makes two or more computer to communicate with each other. This project is about the implementation of e-Lesson Plan Management System for primary school teacher. The system will use client-server system to record daily teaching record and activities. To date, the system is done manually by the teachers, prior to the development of the system; a study has been done so that the teachers can gain a lot of benefit from adopting a suitable Lesson Plan management System. A prototype will be developed and know as e-Lesson Plan Management System (eLPMS). Thus, this project is believed to be useful to all the teachers to manage their lesson plan.